2008
DOI: 10.1128/cvi.00015-08
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Bacillus anthracis Protective Antigen Domains and Efficacy of Elicited Antibody Responses Depend on Host Genetic Background

Abstract: Neutralizing antibodies to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
42
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 51 publications
4
42
0
1
Order By: Relevance
“…This is likely due to the fact that a large number of anti-PA antibodies are directed against non-neutralizing (or possibly even toxin-enhancing) epitopes (29,41). Pioneering work by Little et al (23) suggests that at least 20 antigenic determinants exist on PA. At present, only a few of these epitopes has been described in detail; several have been shown to be targets of monoclonal antibodies (MAbs) capable of effective neutralization in vivo or in vitro (1,8,10,17,44,45). The fact that key neutralizing epitopes on PA remain widely unidentified poses a significant barrier to the evaluation of the efficacy of vaccines based on full-length and truncated PA subunits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely due to the fact that a large number of anti-PA antibodies are directed against non-neutralizing (or possibly even toxin-enhancing) epitopes (29,41). Pioneering work by Little et al (23) suggests that at least 20 antigenic determinants exist on PA. At present, only a few of these epitopes has been described in detail; several have been shown to be targets of monoclonal antibodies (MAbs) capable of effective neutralization in vivo or in vitro (1,8,10,17,44,45). The fact that key neutralizing epitopes on PA remain widely unidentified poses a significant barrier to the evaluation of the efficacy of vaccines based on full-length and truncated PA subunits.…”
mentioning
confidence: 99%
“…This MAb contacts the face of domain 4 that is involved in receptor recognition, and has been proposed to encompass residues 671 to 721. Certainly, additional neutralizing epitopes exist on domain 4 (1,46). In particular, Abboud and Casadevall (1) suggested a linear epitope, immediately adjacent to or possibly overlapping the 14B7 binding site, as the target of neutralizing antibodies.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that a strong humoral response to truncated recombinant PA contributes to a protective immune response to anthrax (3,4). Accordingly, there is considerable interest in ascertaining the location and immunogenicity of B-cell epitopes on the PA molecule.…”
mentioning
confidence: 99%
“…However, A83 exhibited the highest immune response showing that all four domains are required for the maximum protection. Previously, the immunogenicity of different domains has been found variable in within and between genetically different strains of mice 28 . However, in mouse model, domain 1 elicited the highest immune response, whereas domain 2 or 4 were significantly less effective in eliciting the higher antibody titre 28 .…”
Section: Pad1 Pad2 Pad4mentioning
confidence: 99%
“…Previously, the immunogenicity of different domains has been found variable in within and between genetically different strains of mice 28 . However, in mouse model, domain 1 elicited the highest immune response, whereas domain 2 or 4 were significantly less effective in eliciting the higher antibody titre 28 . Because the host genetics plays a very important role in antibody response, therefore domains could elicit different immune response in mouse and human.…”
Section: Pad1 Pad2 Pad4mentioning
confidence: 99%